2013
DOI: 10.1007/s10549-013-2637-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumour diploidy and survival in breast cancer patients with BRCA2 mutations

Abstract: It is not well known to what extent carrying a BRCA2 mutation affects the survival of women with breast cancer and prognostic factors among BRCA2-positive women warrant investigation. Using a record linkage approach we compared the long-term survival in carriers and noncarriers of an inherited BRCA2 founder mutation (999del5), and sought to identify prognostic factors among the BRCA2 mutation-positive subset, including markers of genetic instability (aneuploidy) and mitotic activity (S-phase fraction). We esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
1
20
1
1
Order By: Relevance
“…The pooled, significant, unadjusted HR was 1.57 (95% CI 1.29–1.86) ( Table 3 and S6 Supporting Information, panel H). This survival difference seemed to be driven by one large study [ 62 ], and, when using the best-evidence synthesis, the evidence was still judged to be indecisive. For adjusted breast cancer-specific survival too few HQ studies were available ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled, significant, unadjusted HR was 1.57 (95% CI 1.29–1.86) ( Table 3 and S6 Supporting Information, panel H). This survival difference seemed to be driven by one large study [ 62 ], and, when using the best-evidence synthesis, the evidence was still judged to be indecisive. For adjusted breast cancer-specific survival too few HQ studies were available ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a large scale study involving 2967 patients demonstrated adverse effect of BRCA2 mutations on breast cancer specific survival. (18) These inconsistencies in the research may be due to variations in sample size and the relative rarity of mutation carriers.…”
Section: Introductionmentioning
confidence: 99%
“…We recently published preliminary results that, in breast cancer patients carrying the Icelandic founder mutation 999del5, a positive oestrogen receptor (ER) status predicts an adverse outcome ( Tryggvadottir et al , 2013 ). It is important to verify those results in a larger study, and to find out whether the association between survival and ER status in this genetic subgroup might vary by treatment given.…”
mentioning
confidence: 99%